Effect of heat treatment to clitoria ternatea and hibiscus sabdariffa-based dye-sensitized solar cells' characteristics - Nik Fatin Qistina, Amran; Wan Nur Ainna Amirah, Zulkifli; Alyaa Afiqah, Fauzi; Siti Noor Hidayah, Mustapha; Ahmad Syahiman, Mohd Shah (Institution of Engineering and Technology, 2022)
In this paper, anthocyanin dyes produced from naturally occurring flowers of Clitoria ternatea and Hibiscus sabdariffa were used as sensitizers in dye-sensitized solar cells (DSSCs). The purpose of this study is to analyse the effect of pre-heat treatment towards the I-V performance of these two anthocyanins based-dye as natural dyes of Dye-Sensitized Solar Cell. The photovoltaic characteristics of Clitoria ternatea, Hibiscus sabdariffa and the combination of these flower-based dyes which supposedly produced a new purplish dye are investigated in this paper. The content of anthocyanin extracted from C. ternatea was evaluated using Ultraviolet-Visible Spectrophotometer (UV-VIS) to detect the light absorption behaviour. The performance of DSSCs was analysed with respect to the mix of anthocyanin-based extracts at varied pre-heated temperatures. Interestingly, the efficiency of C. ternatea-sensitized DSSC which the dye was pre-heated at 40 ° C increased significantly at almost 18 times higher than the C. ternatea's sample with non-heated condition. In addition, a new mixture dye of H. sabdariffa and C. ternatea excelled good improved values of cell efficiency, short-circuit current density and fill factor with 0.0023%, 24.244 μA/cm2, and 37.17%, respectively, compared than that of other fabricated samples. This mixed extract exhibited the greatest sensitization in the cell, which was consistent with the extract's broadest spectrum.